Iron status of preterm low birthweight infants and their response to oral iron. Issue 5 (May 1974) - Brozović, B.; Burland, W. L.; Simpson, K.; Lord, Juliet
Abstract : The iron status of a group of preterm low birthweight infants preventively treated with oral iron has been studied by measuring haemoglobin concentration, serum iron concentration, and total iron binding capacity (TIBC) at intervals from birth to 9 months. 47 infants born at an average gestational age of 34 weeks, with a mean birthweight of 1517 g, were investigated. They received 180 mg ferrous sulphate (= 36·3 mg Fe) daily from the fifth week and throughout the study. At 3 months of age most of the infants had low serum iron concentration and increased TIBC indicative of iron deficiency, and over half of them had iron deficiency anaemia (Hb <11 g/100 ml). At 6 and 9 months of age the mean Hb increased slightly, but mean serum iron concentrations remained low, and mean TIBC increased to over 500 μg/100 ml. It is not clear why the amount of iron, administered orally, was insufficient to prevent iron deficiency in almost all the infants, and iron deficiency anaemia in nearly half of the infants studied.